2011
DOI: 10.1093/jmcb/mjr021
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclast precursor differentiation by MCPIP via oxidative stress, endoplasmic reticulum stress, and autophagy

Abstract: Osteoclasts (OCs) are responsible for bone resorption in inflammatory joint diseases. Monocyte chemotactic protein-1 (MCP-1) has been shown to induce differentiation of monocytes to OC precursors, but nothing is known about the underlying mechanisms. Here, we elucidate how MCPIP, induced by MCP-1, mediates this differentiation. Knockdown of MCPIP abolished MCP-1-mediated expression of OC markers, tartrate-resistant acid phosphatase, and serine protease cathepsin K. Expression of MCPIP induced p47(PHOX) and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
93
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 56 publications
2
93
0
Order By: Relevance
“…In this case, it was suggested that autophagy would act as a protective factor reducing cell stress, increasing the formation and viability of osteoclasts. [71][72][73] Deletions in genes encoding key proteins in the formation of the autophagosome (ATG5, ATG7, ATG4B and LC3) have been shown to cause changes in the brush border formation of osteoclasts, and, consequently, to reduce bone resorption and increase bone volume, thus preventing bone loss in mice after ovariectomy. 65 Some authors suggest that inhibition of autophagy in osteoclasts may serve as a possible therapeutic mechanism against bone diseases in which there is an excessive increase in bone resorption.…”
Section: Role Of Autophagy In Bone Biologymentioning
confidence: 99%
“…In this case, it was suggested that autophagy would act as a protective factor reducing cell stress, increasing the formation and viability of osteoclasts. [71][72][73] Deletions in genes encoding key proteins in the formation of the autophagosome (ATG5, ATG7, ATG4B and LC3) have been shown to cause changes in the brush border formation of osteoclasts, and, consequently, to reduce bone resorption and increase bone volume, thus preventing bone loss in mice after ovariectomy. 65 Some authors suggest that inhibition of autophagy in osteoclasts may serve as a possible therapeutic mechanism against bone diseases in which there is an excessive increase in bone resorption.…”
Section: Role Of Autophagy In Bone Biologymentioning
confidence: 99%
“…Osteoclasts, which develop from hematopoietic osteoclast precursors, are the principle cells responsible for bone resorption [3]. Osteoclast precursors are derived from monocytes, which arise in the bone marrow, and differentiate into osteoclasts under influence of M-CSF and RANKL [4,5]. Osteoclast formation and function are increased in osteoporosis [6].…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is a dynamic catabolic process that delivers cellular components to the lysosome for degradation to retrieve molecules and regain energy to maintain cellular homeostasis [24,25]. Recently, reports have shown that the upregulation of autophagy contributes to osteoclastogenesis in response to hypoxic conditions, oxidative stress and microgravity in vitro [5,26,27]. However, the role of autophagy in osteoclast formation and function with glucocorticoid exposure remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is also activated in monocytes exposed to GM-CSF and IL-4 to generate dendritic cells, 1 and to MCP1 to generate pre-osteoclasts. 9 In addition, autophagy is activated in lipid-loaded macrophages (foam cells) found in atherosclerotic lesions 10 For personal use only. on May 12, 2018. by guest www.bloodjournal.org From leading to premature death of the animal.…”
mentioning
confidence: 99%
“…Autophagy was recently observed during osteoclastic differentiation of monocytes exposed to MCP-1. 9 Germ line and somatic mutations in SQSTM1 gene, that encodes the ubiquitin-binding adaptor protein P62/SQSTM1 or sequestosome 1, have been identified in Paget disease of bone. P62/SQSTM1 is a scaffold with multiple protein-protein interaction motifs that plays a role in the signaling pathways activated by RANKL.…”
mentioning
confidence: 99%